1981
DOI: 10.1159/000131597
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of clonal attenuation, clonal succession, and clonal expansion in mass cultures of aging Werner’s syndrome skin fibroblasts

Abstract: Skin fibroblast-like (FL) cells from patients with Werner’s syndrome (adult progeria) demonstrate multiple, stable, structural chromosome rearrangements (variegated translocation mosaicism) which can be used to identify cytogenetically marked clones of cells within a mass culture. We have cytogenetically followed eight FL cell strains (from two patients) throughout their entire in vitro replicative lifespans, and we show a correlation between the expansion and attenuation of individual clones and the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 8 publications
5
27
0
Order By: Relevance
“…Other data support the concept of clonal succession during in vitro passage of human fibroblast cultures (30), and heterogeneity in growth characteristics of clones has been reported by several others (1,4,14,22,24,31). Indeed, it has also been shown that a large proportion of cells in a mass culture possess very limited proliferative capacity (32) and that the maximum MPD of clones which make up the mass culture are bimodally distributed (31, 33).…”
Section: -He Clonat Selection Hypothesissupporting
confidence: 76%
See 1 more Smart Citation
“…Other data support the concept of clonal succession during in vitro passage of human fibroblast cultures (30), and heterogeneity in growth characteristics of clones has been reported by several others (1,4,14,22,24,31). Indeed, it has also been shown that a large proportion of cells in a mass culture possess very limited proliferative capacity (32) and that the maximum MPD of clones which make up the mass culture are bimodally distributed (31, 33).…”
Section: -He Clonat Selection Hypothesissupporting
confidence: 76%
“…Three clones (13,26,32) were assayed only at one stage. Of the remaining clones, two groups could be identified: group A, comprising seven clones (2,10,13,18,29,30,36), in which the error frequency remained relatively constant through subsequent passage although clones 10 and 29 were only assayed singly at two passage levels; group B, comprising two clones (8 and 14) in which an abrupt increase in error frequency at later passage was observed. It bears emphasis that these two clones were the only cases in which an increase in error frequency was observed with passage among all such determinations on mass cultures or clonal populations.…”
Section: Clonal Error Frequenciesmentioning
confidence: 99%
“…A plausible explanation is that this reflects a phenomenon termed clonal succession, described in Salk et al [37]. In this report, mass cultures of skin fibroblasts derived from Werner syndrome patients were examined cytogenetically throughout their entire replicative lifespans.…”
Section: Discussionmentioning
confidence: 80%
“…Death generally occurs in the fifth decade of life, primarily from cancer and cardiovascular disease. Cells from WS individuals have a short replicative lifespan in culture, and exhibit genomic instability characterized by chromosomal variegated translocation mosaicism (Salk et al ., 1981). WRN , the gene defective in WS, encodes a protein that is homologous to the E. coli RECQ helicase, which plays an important role in recombinational repair of DNA damage (Yu et al ., 1996).…”
Section: Introductionmentioning
confidence: 99%